Factores de deserción de los estudiantes en la facultad de enfermería de la universidad de ciencias aplicadas y ambientales U.D.C.A, durante el periodo 2009-2010-i 2011 (2013)
The objective of the research was to identify the economic, academic, cultural and other factors, associated to student dropout in the faculty of nursing at the University of Applied Sciences and Environmental Sciences in each of the cohort of 2009, 2010 and 2011, I. Corresponds to a descriptive study with retrospective quantitative approach, supported by units of the university and the Department of Planning, Admissions and Registration System Academic, and nursing faculty. In the five cohorts 144 deserters were identified, 59 corresponded to the sample. To collect the information an instrument designed by the accompanying program and adapted by the researcher with 33 items, including variables of an individual, personal, socioeconomic and academic type was used. Informed consent was implemented. The results showed the first semester as the moment of the highest number of dropouts, being higher in females between the ages of 16 to 20 years with a 47%. The main causes of dropout were economic factors with 28.8%, followed by academic ones with 22%, the union of economic and academic factors are the third leading cause of attrition with 15.3%, while vocational guidance is in fourth place with 11.9%; lower percentage of factors such as failure to adapt to the universities environment, health conditions such as illness or pregnancy, change of residence to another city, were detected.